Effects of a mindfulness-based intervention (MYmind) for children with ADHD and their parents: protocol for a randomised controlled trial. Issue 11 (12th November 2018) - Chan, Stanley Kam Chung; Zhang, Dexing; Bögels, Susan M; Chan, Christian Shaunlyn; Lai, Kelly Yee Ching; Lo, Herman Hay Ming; Yip, Benjamin Hon Kei; Lau, Elsa Ngar Sze; Gao, Tiffany Ting; Wong, Samuel Yeung Shan
Abstract : Introduction: Mindfulness is one of the potential alternative interventions for children with attention-deficit hyperactivity disorder (ADHD). Some evidence suggests that mindfulness is related to changes in brain regions associated with ADHD. The potential benefits of mindfulness on children with ADHD, as well as the feasibility of this intervention approach, are warranted through prior local and foreign studies. This study aims to evaluate the effect of mindfulness-based group intervention for children with ADHD and their respective parents through a robust research design. Methods and analysis: This study will adopt a randomised controlled trial design including 140 children aged 8–12 years with ADHD together with one of their parents (n=140). These families will be randomised into intervention group (n=70) who will be offered the MYmind programme delivered by trained healthcare professionals, and an active control group (n=70) who will be offered the CBT programme. The intervention includes 8 weekly 90 min group sessions for children with ADHD (aged 8–12 years) and their respective parents. The primary and secondary outcomes will include children's attention, ADHD-related symptoms, behaviours, executive function and mindfulness levels measured by validated objective measures and parent's reported instruments. Parents' parental stress, parenting styles, ADHD related symptoms, well-being, rumination level and mindfulness levels will also be measured. Analysis is by intention to treat. The effects of intervention will be evaluated by comparing outcomes between the two arms, as well as comparing outcomes within subject through comparing measurements at baseline (T0), immediately after the 8 week intervention (T1) and at 3 (T2) and 6 (T3) months postintervention. Ethics and dissemination: Ethics approval has been granted by the Joint Chinese University of Hong Kong – New Territories East Cluster Clinical Research Ethics Committee (The Joint CUHK-NTEC CREC). Participants will be required to sign informed consent form from both parents and children. Findings will be reported in conferences and peer-reviewed publications in accordance with recommendations of Consolidated Standards of Reporting Trials. Trial registration number: ChiCTR1800014741; Pre-results.